Pengaruh Pemberian Terapi Aktivitas Kelompok Sosialisasi Terhadap Perubahan Perilaku Klien Isolasi Sosial : The Effect of Socialization Group Activity Therapy Changes in Behavior of Social Isolation Clients - Surya Efendi; Atih Rahayuningsih; Wan Muharyati (Fakultas Keperawatan Universitas Andalas, 2012)
This study aims to determine the Effect of Activity Group Therapy: Socialization (AGTS) to Client Behavior Change Social Isolation in Gelatik Room Prof. HB Sa'anin Mental Hospital Padang. This study used a quasi-experiment design without a control group with the approach of one group pretest and posttest design. Objects in this study are the client's social isolation. Sampling was purposive sampling with a sample of 10 people. Instruments used in the form of sheets of observation and interview guides. Clients of social isolation pretest were conducted before being given AGTS, then do the posttest. The average value of the pretest was 31.5, and the posttest mean value was 40.1. This shows a decline in social isolation behavior after being given the AGTS. Data were analyzed using Two Different Tests Mean Dependent (Paired Samples) with a 95% degree of confidence. The results of statistical tests obtained p = 0.00 (p <0.05). This suggests there is a significant influence on the administration AGTS to changes in client behavior of social isolation. It is expected for hospital nurses to be able to improve the implementation of AGTS with respect to indications that the client can participate in the activities of the AGTS. Then the researchers next need to be examined by using qualitative techniques.